The Kinesics of Infinity Laban, Geometry and the Metaphysics of Dancing Space - Counsell, Colin (Edinburgh: Edinburgh University Press, 2006)
RESUMEN: The historical emergence of modernist dance is well documented, but locating its kinesics in history often proves more challenging. The forms and gestures characteristic of Rudolf Laban's practice, for example, were emphatically nonmimetic, not conductive to the representation of any recognizable historical reality. They nevertheless proved resonant for performers and audiences alike, and so clearly spoke to some form of perception, a way of conceptualizing the body's actions that was accessible to a diversity of social subjects. If they cannot be seen as representation, then, they still comprised acts of ideation, and positioning them in history will entail locating their founding historical rationale, the mode of thought linking apparently subjective response to the social, the aesthetic object to its viewer. It is this species of thought, at once social and aesthetic, that Raymond Williams described with his term "structure of feeling".